Cervicogenic headache. Longitudinal observational study on 553 patients - Claudio Santoro; Michela D'Oro (Publiediting, 2022)
Cervicogenic headache is a common disorder affecting about 68 per cent of adults in Europe (53 per cent headache and 15 per cent migraine), of which around 2-5 per cent are chronically refractory.1 Patients who suffer from it are often induced to use over-the-counter drugs with even serious consequences: in addition to predisposing complex comorbidities, improper use of medications significantly influence both the progression of the disease (chronicity) and the therapeutic strategies. The study (longitudinal observational) refers to the 553 requests for intervention for headache (or neck pain) received by our center in the period January-December 2019. The data collected made it possible to recognize the headache as generated by the functional lesions of certain neuro-musculoskeletal and vascular districts (classified as DC1, DC2, DC3), in turn connected to the functional block (also known as joint facet conflict, block in malposition or subluxation) of the articular processes of C0-C1-C2 -C3. Manual medicine has proved to be effective in the treatment of acute, subacute and chronic phases.